2012
DOI: 10.2298/sarh1210595p
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum adiponectin and leptin concentrations with anthropometric parameters in newborns

Abstract: Significantly higher adiponectin levels were found in AGA neonates compared to SGA neonates. Leptin and adiponectine levels were positively correlated with birth weight. These findings suggest that these adipocytokines may be involved in fetal growth regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
2
4
2
Order By: Relevance
“…The positive association detected in this study between the leptin concentration in the maternal serum and umbilical cord and neonatal anthropometric measurements confirms what was reported in the previous studies [9,17,30,50]. Schubring et al [30] detected a significant correlation between leptin levels in the umbilical vein and artery and birth weight of the neonates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive association detected in this study between the leptin concentration in the maternal serum and umbilical cord and neonatal anthropometric measurements confirms what was reported in the previous studies [9,17,30,50]. Schubring et al [30] detected a significant correlation between leptin levels in the umbilical vein and artery and birth weight of the neonates.…”
Section: Discussionsupporting
confidence: 91%
“…As other studies have reported, in our study the mean leptin concentrations were also higher in female neonates than in male neonates even though the birth weight in both sexes was similar. This may suggest participation of sex hormones in leptin secretion [17,50,51]. This is contrary to the study results published by Palcevska-Kocevsa et al [50], who found no differences in the leptin concentrations between the male and female infants.…”
Section: Discussioncontrasting
confidence: 58%
“…Our study in newborns showed that leptin and adiponectin levels were positively correlated with all anthropometric parameters: body weight, body length, BW/BL, BMI, and the pondered index (p<0.01). These results indicate that the stage of body growth maturity is positively correlated to adipocytokines involved in fetal growth regulation, as previously reported ( 27 , 36 , 37 ). SGA newborns have the riskiest metabolic profile among all other newborn groups.…”
Section: Discussionsupporting
confidence: 90%
“…Child adiponectin levels at birth and birth weight have been examined in the previous studies however, were inconsistent. Volberg et al reported no relations (Volberg et al 2013), while the others reported positive association between cord MINATOYA 5 blood adiponectin levels with birth weight (Mantzoros et al 2009) and the association between lower adiponectin and small for gestational age (SGA) and preterm birth (Palcevska-Kocevska et al 2012;Yeung et al 2015). A progressively significant negative association between adiponectin and BMI at 2, 5, and 9 years of age has been reported (Volberg et al 2013).…”
Section: Minatoyamentioning
confidence: 99%